ENTREPRENEURIAL OPPORTUNITIES IN AGRICULTURE AND ALLIED SECTORS IN ASSAM - Tamuli, Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Agriculture and allied sectors always play a crucial role in the economy of India. It serves as a primary source of livelihood for a significant portion of Indian population. The sector which contributes to Gross development product by producing raw materials for meeting human and animal needs has been facing different challenges such as small landholdings by farmers, outdated practices, low productivity, pest control and climate variability. Agriculture entrepreneurship is the best way to address these issues and enhances the overall contribution of agriculture to economic growth. It fosters innovation and sustainable practices in the agricultural sectors. The diverse agro-climatic zones and rich biodiversity of Assam presents promising agripreneurship opportunities. Assam has notable potential in different segments such as sericulture, tea industry, animal husbandry, organic farming, horticulture, floriculture, aquaculture. spice cultivation, handicraft etc. In this paper an attempt has been made to examine the challenges and opportunities of agriculture entrepreneurship in Assam.